Antibody response to the messenger RNA‐1273 vaccine (Moderna) in liver transplant recipients. Issue 7 (28th March 2022) - Cuadrado, Antonio; del Barrio, María; Fortea, José Ignacio; Amigo, Lidia; San Segundo, David; Rodriguez‐Cundin, María Paz; Rebollo, María Henar; Fernandez‐Santiago, Roberto; Castillo, Federico; Achalandabaso, Maria; Echeverri, Juan; Anderson, Edward J.; et al.
Abstract: Different reports have shown the clinical and serologic response to the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) messenger RNA (mRNA) vaccines in preventing coronavirus disease 2019 (COVID‐19) in the general population, but few studies have examined these responses in transplant recipients. We assessed the vaccine immunogenicity of two doses (100 μg) of the mRNA‐1273 vaccine (Moderna) administered with a 28‐day interval in liver transplant recipients (LTRs) at follow‐up at the Marques de Valdecilla University Hospital. LTRs without a history of COVID‐19 infection were tested for SARS‐CoV‐2 immunoglobulin G (IgG) antibodies directed against the spike protein (S) a median of 43 days after receiving the second Moderna vaccine dose. Clinical data, including immunosuppressive regimen and routine laboratory data, were obtained from the medical record of each patient up to 3 months before the date of the first vaccination. Factors associated with serologic response were evaluated through logistic regression. In total, 129 LTRs who had anti‐S results were included. Most patients were men (n = 99; 76.7%) with a median age of 63 years (interquartile range, 56–68). Alcohol (43.4%) and chronic hepatitis C (18.6%) were the most frequent causes of liver transplantation. A positive anti‐S IgG response was observed in 113 LTRs (87.6%; 95% confidence interval [CI], 80.8–92.2). A strong inverse relationship between mycophenolate mofetil use and serologic response was found (odds ratio, 0.07; 95% CI, 0.02–0.26; p = 0.001). Conclusion: Most LTRs develop an immunological response to the Moderna SARS‐CoV‐2 mRNA‐based vaccine. An immunosuppressive regimen that includes mycophenolate predicts a weak serologic response. Abstract : Two doses of a mRNA‐1273 vaccine (Moderna) against the SARS‐Cov‐2 virus in liver transplant recipients induce a high serological response [87.6%; (95% CI = 80.8 – 92.2)]. Immunosuppression with mycophenolate impairs this response.image